Copper-Catalyzed Asymmetric 1,6-Addition of Borylalkene-Derived Nucleophiles to para-Quinone Methides - Meng, Deyuan; He, Jing; Yoon, Woojin; Yun, Hoseop; Han, Jung Tae; Yun, Jaesook (Advanced Synthesis and Catalysis, 2022)
Herein, we report the catalytic 1,6-addition of chiral alkyl copper nucleophiles, in-situ generated from borylalkenes and a copper-hydride catalyst under mild conditions. Chemo- and stereoselective control was crucial in this reductive coupling process of borylalkenes and para-quinone methides, sequentially forming adjacent stereogenic centers with good diastereo- and enantioselectivity. Through the multicomponent and catalytic tandem reactions, asymmetric 1,6-adducts of p-quinone methides were efficiently synthesized. (Figure presented.).
Keywords: Asymmetric Catalysis; Conjugate Addition; Copper; para-Quinone Methides; Reductive Coupling